Involvement of supralemniscal nucleus (B9) 5-HT neuronal system in nociceptive processing: a fiber photometry study - Shunpei Moriya; Akira Yamashita; Daiki Masukawa; Yuki Kambe; Junichi Sakaguchi; Honami Setoyama; Akihiro Yamanaka; Tomoyuki Kuwaki (Molecular Brain, 2020)
Abstract Nociception is important perception that has harmful influence on daily life of humans. As to main pain management system, some descending pathways are called descending antinociceptive systems (DAS). As main pathways of DAS, it is well known that dorsal raphe (B6/B7) - rostral ventromedial medulla (B3) - spinal dorsal horn includes serotonergic system. However, possible role of supralemniscal (B9) serotonin (5-HT) cell group in pain management is still open question. In this study, we measured activities of B9 5-HT neuronal cell bodies and B9 5-HT neuron-derived axons located in the locus coeruleus (LC) and ventral tegmental area (VTA), which are also main players of pain management, using fiber photometry system. We introduced the G-CaMP6 in B9 5-HT neurons using transgenic mice carrying a tetracycline-controlled transactivator transgene (tTA) under the control of a tryptophan hydroxylase-2 (TPH2) promoter and site-specific injection of adeno associated virus (AAV-TetO(3G)-G-CaMP6). After confirmation of specific expression of G-CaMP6 in the target population, G-CaMP6 fluorescence intensity in B9 group and LC/VTA groups was measured in awake mice exposed to acute tail pinch and heat stimuli. G-CaMP6 fluorescence intensity rapidly increased by both stimuli in all groups, but not significantly reacted by nonnociceptive control stimuli. The present results clearly indicate that acute nociceptive stimuli cause a rapid increase in the activities of B9-LC/B9-VTA 5-HTergic pathways, suggesting that B9 5-HT neurons play important roles in nociceptive processing.